Cytogenetic stability and genome size variations in newly developed derived Brassica juncea allopolyploid lines (Journal of Oilseed Brassica, 2026)
Allopolyploids are normally resynthesized through interspecific hybridization and whole genome duplication. Brassica group has developed a new concept of derived digenomics, where an allopolyploid Brassica is synthesized through hybridization of two nonparental digenomic species. Genetic differences in allopolyploids result from recombination between the hybridized subgenomes or structural variation in cohabiting genomes which can significantly impact genetic constellations and consequently the phenotype. We analysed 62 Brassica juncea progenies, developed following hybridization between B. napus and B. carinata, for cytogenetic stability and genome size changes in S5 and S6 generations. In derived B. juncea genotypes, pollen grain stainability ranged from 65 to 95 percent. Meiotic analysis of the derived B. juncea lines conducted during S5 and S6 generations revealed standard 18II configuration for the majority of test genotypes. During S5 generation, some genotypes revealed abnormal meiotic configurations. These genotypes were: DJ 1-1, DJ 22, DJ 25, DJ 115, DJ 116 (all 18II+1I), DJ 21 and DJ 19-2 (both 19II) and DJ 55 (17II). All these genotypes generally had monosomic or disomic addition of, possibly, one chromosome each from C genome. Anaphase I distribution was also aberrant in these genotypes. This perhaps caused impaired pollen fertility. One generation of selfing and selection for improved fertility, however, led to correction of meiotic aberrations in all these instances. All the derived B. juncea genotypes were crossed as female with natural B. juncea to identify random chromosome substitutions. All the consequent F1 genotypes were cytologically analysed during meiosis1. Occurrence of 17II and 2I in the F1with natural euploid B. juncea was considered to be indicative of substitution for one chromosome pair. Disomic chromosome substitution was indicated for DJ 15, DJ 18, DJ 19-2, DJ 21, DJ 38, DJ 58, DJ 61, DJ 92, DJ 97, DJ 103 and DJ113. Molecular characterization helped to resolve these substitution lines into six distinct groups. Most of these substitution lines are expected to involve A/ C substitutions. Genome size variations were also observed. On the basis of population mean (over 62 derived juncea types), average genome size was 528.274 Mbp, representing a decline of almost 1.072 percent DNA during six generations of selfing following allopolyploidization. These studies confirmed the viability of the concept of developing derived amphiploids.